Management of boxers fracture with single antegrade bent K-wire - Sadiq, Mohammed; Hussain, Syed Azher (International Journal of Research in Orthopaedics, 2019)
Background: Fractures of the neck of fifth metacarpal are commonly encountered in orthopaedic practice. Management of these fractures is a debatable topic with treatment varying from conservative management to surgical fixation. In our study we used a pre-bent k wire in antegrade fashion to achieve fracture fixation. We found that pre-bent K wire provides an excellent reduction with good correction of neck shaft angle and good restoration of movements at the metcarpo-phalyngeal and inter-phalyngeal joints. Pre-bent K wire provides an efficient and economical modality of fixation in fracture neck of fifth metacarpal fractures. Methods: All patients presenting with fracture neck of fifth metacarpal were managed by pre-bent K wire in antegrade fashion by a single surgeon using a single prebent K wire. Results: All the fractures involved the dominant hand (16 right and 6 left). The mean duration of surgery was 24 mins. Intra operatively the mean no of X ray shoots were 12. At the end of the follow-up there was no significant difference in the TAM in the affected and the unaffected hand. The p=0.17. The mean DASH at the end of the follow up was 2.42. The mean fracture healing time was 45 days. Conclusions: Boxers fracture is very common fracture type in young active adults. Conservative management is usually associated with shorting and angular deformities. Percutenous fixation of the fracture with bent K wire placed in antegrade fashion provides good stability at the fracture site.